Dynamics Of Legal Protection Of Foreign Workers In The Era Of Globalization In Indonesia - Mashari, Mashari; Retno Mawarini Sukmariningsih; Indriyasari, Indriyasari; Sriyanti, Sriyanti; Imam Subiyanto; Tubagus Achmad Darodjat (International Journal of Education, Vocational and Social Science, 2024)
The purpose of this study is to analyze the legal protection of Foreign Workers (TKA) which is difficult to avoid due to investment activities in the context of national development and for the mastery and transfer of technology as a continuous and ongoing process so that it is possible to use TKA, in addition to the lack of Indonesian Migrant Workers (TKI) who are experts and skilled to replace TKA. The problems in this study include: Regulation of TKA in the era of globalization , and the dynamics of legal protection of Foreign Workers in the era of globalization in Indonesia . The research method uses a normative legal research type, a study that uses secondary data and primary data. The results of the study show that: First, the regulation of foreign workers in the era of globalization in Indonesia has been regulated in Government Regulation Number 34 of 2021 concerning the Use of Foreign Workers, and Law Number 6 of 2023 concerning Job Creation in licensing foreign workers made easier . Second, the dynamics of legal protection of foreign workers in the era of globalization in Indonesia Based on the work agreement, foreign workers also receive social security as regulated in Article 1 number 4 of Law Number 24 of 2011, which in essence stipulates that social security participants are every person, including foreigners who work for at least 6 (six) months in Indonesia and are required to be provided with protection through national social security. Government policy has removed several regulations that hinder investment progress through deregulation of foreign worker use policies to increase foreign investment in Indonesia.